Pengaruh Penyakit Hipertensi Terhadap Kualitas Fungsi Ginjal (Studi Literatur) - Andi Arfah; Andi Hariati; Andi Agustang (Journal of Health Quality Development, 2021)
Changes in the current human lifestyle are one of the causes of declining quality of life due to the lack or inability of the body to respond to the internal and external environment, which in turn will cause health problems, both local and systemic. The availability of facilities that facilitate affordability of access to services is one of the causes of a person’s lack of activity, coupled with an unhealthy diet with fast food intake as a manifestation of disturbances in body organs, including impaired heart and blood vessel function. The purpose of this study was to review research journals on the effect of hypertension on the quality of kidney function. The research design used a literature study method by taking references from several research journal sources related to the effect of hypertension on the quality of kidney function. From the results of the study as a reference for this study, there was an effect of hypertension on chronic kidney disease. Hypertension can cause chronic kidney disease, and can worsen chronic kidney disease.